(untitled) (International Journal of Management and Sustainability, 2014)
Nowadays, competition is everywhere in the business environment. The survival of Small and medium-sized enterprises (SMEs) depend on their ability to take full advantage of the resources available. Prior research had identified that IT is an important resource to the success of the firms. However, despite the common consensus that IT influences firm’s performance, results of previous studies on the effect of IT resources on firm’s performance are often inconsistent. Given these inconsistent results, it is unclear whether any direct effect exists between IT resources in organizations and their firm’s performance. For that reason, several authors highlighted the need for more research to investigate the impact of IT adoption on the firm’s performance. In response to this, this conceptual paper attempts to analyze relevant literatures on whether IT investment would help firms gain better performance. Understanding whether and how IT has affected firm’s performance is an important research issue as it allows the firms to know the value of IT investment and whether such innovation is worth to be adopted. Grounding in RBV theory, this study concluded that the combination of IT assets and IT capabilities (IT infrastructure) provides competitive advantage to the firm. This study also suggested that SMEs that adopt IT would perform better than those that do not adopt IT. This conceptual analysis is hoped to consolidate the body of knowledge in the area and significant to the researchers as it directs to the hypotheses development for future research.